Measures of outcome for stimulant trials: ACTTION recommendations and research agenda. (1st January 2016) - Kiluk, Brian D.; Carroll, Kathleen M.; Duhig, Amy; Falk, Daniel E.; Kampman, Kyle; Lai, Shengan; Litten, Raye Z.; McCann, David J.; Montoya, Ivan D.; Preston, Kenzie L.; Skolnick, Phil; Weisner, Constance; et al.
Highlights: Meaningful outcome measures, other than sustained abstinence, would be beneficial. There are multiple challenges unique to measuring stimulant use. Meaningful alternative outcomes should be associated with functional benefits. A patient reported outcome may be useful for validating a stimulant use endpoint. Abstract: Background: The development and approval of an efficacious pharmacotherapy for stimulant use disorders has been limited by the lack of a meaningful indicator of treatment success, other than sustained abstinence. Methods: In March, 2015, a meeting sponsored by Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks (ACTTION) was convened to discuss the current state of the evidence regarding meaningful outcome measures in clinical trials for stimulant use disorders. Attendees included members of academia, funding and regulatory agencies, pharmaceutical companies, and healthcare organizations. The goal was to establish a research agenda for the development of a meaningful outcome measure that may be used as an endpoint in clinical trials for stimulant use disorders. Results and conclusions: Based on guidelines for the selection of clinical trial endpoints, the lessons learned from prior addiction clinical trials, and the process that led to identification of a meaningful indicator of treatment success for alcohol use disorders, several recommendations for future research were generated. These include a focus on the validation of patient reported outcome measures of functioning, the exploration of patterns of stimulant abstinence that may be associated with physical and/or psychosocial benefits, the role of urine testing for validating self-reported measures of stimulant abstinence, and the operational definitions for reduction-based measures in terms of frequency rather than quantity of stimulant use. These recommendations may be useful for secondary analyses of clinical trial data, and in the design of future clinical trials that may help establish a meaningful indicator of treatment success.